Using text-mined trait data to test for cooperate-and-radiate co-evolution between ants and plants - Kaur, Katrina M.; Malé, Pierre-Jean G.; Spence, Erik; Gomez, Crisanto; Frederickson, Megan E. (PLOS Computational Biology, 2019)
Author summary Many plants and animals depend on other species for nutrition, protection, or dispersal, a type of ecological interaction known as mutualism. Mutualisms often help organisms thrive in new or harsh environments, thereby increasing their ecological success. We studied whether mutualism also increases evolutionary success by affecting lineage diversification, or the net result of the formation and loss of species over evolutionary time (i.e., speciation minus extinction). We focused on the widespread mutualism between ants and plants, in which ants act as protective ‘bodyguards’ or seed dispersers for plants and gain food or shelter in return. Previous research has found that the evolution of ant-plant mutualisms increased plant diversification. Here, we asked whether the same is true for ant diversification. We used a novel, automated approach to gather trait data from the abstracts of over 89,000 scientific articles about ants, and identified 432 mutualistic ant species and 2,909 non-mutualistic ant species. We then used this trait information to model how mutualism has evolved and influenced diversification across a recent ant phylogeny. Our analysis suggests that instead of causally enhancing diversification, mutualism evolves more often in lineages that are already diversifying quickly and then slows ant diversification.